Improving Business Model Canvas (BMC) With The Approach Of Strength, Weakness, Opportunity And Threat Factors At Seymour Business Unit - Taufiqulloh, Rifqi; Pasaribu, Rina Djunita (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Seymour is a business unit engaged in the footwear business located in the city of Bandung. Currently, Seymour needs help in the form of declining sales due to customer purchasing behavior preferring online shopping and high competition. Other problems include high costs due to relatively unproductive offline stores. Seymour also needs a comprehensive business strategy/model. This research proposes a new improvement program for Seymour's Business Model Canvas. In formulating the program, the approach used is to analyze the strengths, weaknesses, opportunities, and threats of the nine blocks of the Business Model Canvas. Based on the research results, Seymour has fulfilled the nine blocks of the Business Model Canvas. From the analysis of the Business Model Canvas's strengths, weaknesses, opportunities, and threats, Seymour has 15 strengths and five weaknesses for internal factors. In contrast, Seymour has eight opportunities and nine threats for external factors. After conducting the analysis, the matching was carried out and resulted in 11 improvement programs. Grouping was then carried out from all 11 improvement programs, resulting in 9 improvement programs for the new Business Model Canvas. Of all the Business Model Canvas improvement programs, there are five priority improvement programs: adding customer segments, adding product variations, adding sales channels, creating new unique values, and adding human resources.